Diet Diversity Score may not be a Good Indicator of Healthy Diet - Masoumeh Akhlaghi (Shiraz University of Medical Sciences, 2017)
Background: The close relationship between diet and disease emphasizes the need for optimal diet evaluation. The aim of this study was to compare the efficiency by which each of Healthy Eating Index (HEI)-2010, Diet Quality Index-International (DQI), Mediterranean Diet Score (MDS), and Diet Diversity Score (DDS) evaluates the diet. Methods: In a cross-sectional design, 438 adults aged 20-50 years were recruited. Dietary intakes were assessed using a semi-quantitative food frequency questionnaire. HEI-2010, DQI, MDS, and DDS were calculated and scored according to their corresponding criteria. Results: Energy (1917 ± 554 kcal to 2898 ± 933 kcal), saturated fats (17.0 ± 6.8 g to 28.1 ± 11.5 g), and cholesterol (244 ± 195 g to 414 ± 343 g) increased across tertiles of DDS and energy (2017 ± 699 kcal to 2621 ± 748 kcal) increased across tertiles of DQI. In contrast, saturated fats decreased (23.9 ± 12.0 g to 20.8 ± 8.1 g for HEI-2010 and 23.7 ± 10.0 g to 20.5 ± 10.4 g for MDS), but energy and cholesterol did not change significantly across tertiles of HEI-2010 and MDS. Other nutrients either did not change or changed appropriately across tertiles of the different indices. Conclusion: DDS and, to a less extent, DQI may not be good indicators of healthy diet especially in terms of obesity and cardiovascular diseases.